The Application of the Numbered Heads Together (NHT) Cooperative Learning Model to Improve Memory in Learning Degree of Comparison among Grade XI-C1 Students at SMAN 2 Pamekasan - Hanadi Putri; Khodatul Jannah; Lukluk Ibana; Dinar Vincy Yunitaka B; Laily Laily (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This classroom action research aims to improve students' memory in learning the "Degree of Comparison" material by implementing the Numbered Head Together cooperative model. The study was conducted at SMAN 2 Pamekasan with 34 students of class XI-C1 as subjects. The research was carried out in two cycles consisting of planning, action, observation, and reflection. Data were collected through observation, test, and documentation. The indicators measured included two cognitive aspects, namely: (1) ability to recall comparative and superlative structures, task completion accuracy, cooperation in group work, and adherence to instructions. The results showed a significant increase in students' memory levels. At the pre-cycle stage, only 11.8% of students were in the high category, in cycle I increased to 44.1%, and in cycle II reached 73.5%. This proves that the NHT model is effective in improving students' memory and understanding of English grammar topics and is expected to develop collaborative learning.